2012
DOI: 10.1007/s11665-012-0146-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties and Wetting Behavior of High Temperature Zn-Al-In Solders

Abstract: Solders for ultrahigh-temperature applications were defined by Vianco as those able to sustain working conditions with temperatures as high as 573 K, with momentary temperature rise up to 623 K. Zn-Al eutectic alloy (12 at.% Al) fits such defined criteria with respect to its melting temperature. It was found that small additions of indium to Zn-Al eutectic lower its melting temperature. The aim of this work is to assess if and to what extent thermal properties and wetting behavior are affected. It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 16 publications
0
27
1
3
Order By: Relevance
“…With increased Cu, the electrical resistivity of the eutectic ZnAl alloy also increased. In comparison to the data on electrical resistivity for ZnAl with In, [7] the values obtained here are lower. The linear expansion of ZnAl alloys with added Cu shows the same pattern as the electrical resistivity, with increased Cu in alloys increasing the CTE.…”
Section: Resultscontrasting
confidence: 72%
See 3 more Smart Citations
“…With increased Cu, the electrical resistivity of the eutectic ZnAl alloy also increased. In comparison to the data on electrical resistivity for ZnAl with In, [7] the values obtained here are lower. The linear expansion of ZnAl alloys with added Cu shows the same pattern as the electrical resistivity, with increased Cu in alloys increasing the CTE.…”
Section: Resultscontrasting
confidence: 72%
“…The precipitates were analyzed and identified, using XRD, as b-CuZn, c-Cu Zn12Al1.5Cu Zn5.3Al1.57Cu 657.9 (384.9) Fig. 1-Electrical resistivity vs temperature of pure Zn, [7] eutectic ZnAl, [7] and ZnAl with Cu alloys.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a higher amount of the eutectic phase is the reason of higher electrical resistivity. Gancarz et al (Ref 3,16) found that the electrical resistivity of Zn-Al-In and Zn-Al-Ag increases as temperature rises and different metal components are added: from 6.5 to 8.5 lX cm at room temperature for Zn-Al-xIn (x = 0.5-1.5 wt.%) and 6.5-7.2 lX cm for Zn-Al with addition of Ag 3.1.5 Mechanical Properties. Tensile test was used to evaluate the mechanical properties of the as-cast Zn-Al-Si alloys compared with the strength of eutectic ZnAl solder.…”
Section: Characteristics Of Cast Alloysmentioning
confidence: 99%